The effect of smart contracts (blockchain technology) on Jordan’s land registry and survey department for sustainable development - AbdelKarim Fawwaz AlBataineh (Discover Sustainability)
Abstract This study explores the implementation of blockchain technology, specifically smart contracts, within the Land Registry and Survey Department to enhance sustainable development in Jordan. Utilizing a quantitative, cross-sectional survey design, the research targeted 12,450 employees of the Jordanian Department of Lands and Survey, with a stratified random sample of 448 respondents. The data, gathered through online surveys and analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM), reveals significant positive relationships between blockchain implementation facets—such as Security and Fraud Prevention, Efficiency and Automation, Regulatory Compliance, Transparency and Trust, and Accessibility and User Experience—and sustainable development outcomes. Despite these promising results, the study acknowledges critical challenges such as the need for technical expertise, regulatory frameworks, and initial investment hurdles. Addressing these challenges is crucial for balanced implementation and sustained engagement with the technology. The model accounts for 77.6% of the variance in sustainable development, highlighting blockchain's potential to simultaneously tackle multiple land administration challenges. This research provides empirical evidence of blockchain's impact on sustainable development, offering a comprehensive framework for its application in land registries, particularly in developing nations. The findings hold significant implications for policymakers, land registry administrators, and technology implementers, underscoring the importance of integrating technological innovation within existing regulatory and institutional contexts to achieve sustainable economic, environmental, and social growth.